Answer:
The slope intercept form of both given equations is : y = - 3 x - 4.
Step-by-step explanation:
Here, the given equations are:
y +7 = -3 ( x - 1 )
and 3 x + y = - 4
Now,the SLOPE INTERCEPT FORM of any given equation is given as:
y = m x + C : here, C = Y - intercept, m = Slope
Consider equation (1):
y +7 = -3 ( x - 1 ) ⇒ y + 8 = - 3 x + 3
or, y = -3x + 3 - 7 = -3x - 4
⇒ y = -3x -4
Hence, the slope-intercept form of the given equation is y = -3x -4.
Consider equation (2):
3 x + y = - 4 ⇒ y = -4 - 3 x
⇒ y = -3 x - 4
Hence, the slope-intercept form of the given equation is y = -3x -4.
My final answer is automatic 588
Answer:
3 • (2xy - 7) • (xy + 2)
Step-by-step explanation:
(((2•3x2) • y2) - 9xy) - 42
6x2y2 - 9xy - 42 = 3 • (2x2y2 - 3xy - 14)
Answer:
2/3
Step-by-step explanation:
use rise over run. you may pick two y values and 2 x values and say (y2-y1)/(x2-x1). here I used (3-1)/(3-0)